2008
DOI: 10.1111/j.1365-2559.2007.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vascular tumours: an update

Abstract: This review evaluates changes in vascular nomenclature particularly in the category of vascular tumours of intermediate malignancy that includes the various haemangioendotheliomas, Kaposi's sarcoma and giant cell angioblastoma. Recently described entities in this category, including the latter tumour and composite haemangioendothelioma, are described. Several newly characterized vascular tumours not included in recent classifications of vascular tumours are also summarized. These include acquired elastotic hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 68 publications
2
72
0
4
Order By: Relevance
“…The epidermis is unremarkable or atrophic. The most attractive feature is the intense accompanying solar elastosis which is surrounding or intermingled with the capillaries [1][2][3]. Immunohistochemical studies demonstrated the endothelial nature of the neoplastic cells which are usually positive for CD31 and CD34 markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidermis is unremarkable or atrophic. The most attractive feature is the intense accompanying solar elastosis which is surrounding or intermingled with the capillaries [1][2][3]. Immunohistochemical studies demonstrated the endothelial nature of the neoplastic cells which are usually positive for CD31 and CD34 markers.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, aquired elastotic hemangioma may be confused with a superficial basal cell or Bowen's disease [1]. Histologically, the classic finding is a band-like proliferation of capillary blood vessels arranged parallel to the epidermis and confined to the superficial dermis [3]. The vessels contain well formed round or elongated lumens lined by a single layer of monomorphous endothelial cells without any atypia or mitosis surrounded with a layer of pericytes.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid angiosarcoma shows diffuse rather than localized nuclear atypia and more marked mitotic activity. Epithelioid HE also has a propensity for the head and neck region, but may present multicentrically and more frequently involves deep soft tissues, solid organs and bone [27,28], while primary presentation in the skin is rare [29]. About half of EHE are associated with a medium-sized or large vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hemangiomas differ as they are fully grown by birth and do not have the characteristic postnatal rapid growth phase, tending to involute after 1 year [12]. Histologically, hemangiomas contain plump epithelial cells and lobules of benign-appearing capillaries, and have markers for vascular tumors [2,15]. Vascular malformations can have similar clinical presentation at birth, but do not have the rapid growth pattern.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Hemangiomas are the most common tumor of infancy, occurring in 4% to 10% of infants [2,15,40], and approximately 15% of these lesions involve the extremities. Congenital hemangiomas differ as they are fully grown by birth and do not have the characteristic postnatal rapid growth phase, tending to involute after 1 year [12].…”
Section: Discussion and Treatmentmentioning
confidence: 99%